The occurrence of the strongylid nematodes Kalicephalus brachycephalus, K. bungari and K. indicus in snake species from Hunan Province, China. Issue 3 (18th May 2016) - Liu, W.; Wang, T.; Liu, T.B.; Tan, L.; Lv, C.C.; Liu, Y.
Abstract: Kalicephalus is a genus of strongylid nematodes infecting snakes and causing serious diseases and even death when it is complicated with secondary bacterial infections. The infection of snakes with Kalicephalus has been reported in many countries in the world. However, little information is available on the prevalence of Kalicephalus in snakes in China. In the present study, the prevalence of Kalicephalus in snakes was investigated. The worms were examined, counted and identified to species according to existing keys and descriptions. Three species of Kalicephalus, namely K. indicus, K. bungari and K. brachycephalus, were found in six species of snakes ( Elaphe carinata, Zaocys dhumnade, Naja najaatra, Elaphe taeniura, Bungarus multicinctus and Dinodon rufozonatum ). The total prevalence of Kalicephalus in snakes in Hunan Province was 39.7%. The most common species was K. indicus, with the highest prevalence 72.8%, followed by K. bungari (24.0%). The prevalence of K. brachycephalus was 0.9%. This is the first report on the prevalence of Kalicephalus species in snakes in China, and the findings have important implications for the control of Kalicephalus infections in snakes in China.